2007
DOI: 10.1104/pp.107.098665
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Expression Profiling of Rice Grain Filling-Related Genes under High Temperature Using DNA Microarray

Abstract: To elucidate the effect of high temperature on grain-filling metabolism, developing rice (Oryza sativa) 'Nipponbare' caryopses were exposed to high temperature (33°C/28°C) or control temperature (25°C/20°C) during the milky stage. Comprehensive gene screening by a 22-K DNA microarray and differential hybridization, followed by expression analysis by semiquantitative reverse transcription-PCR, revealed that several starch synthesis-related genes, such as granule-bound starch synthase I (GBSSI) and branching enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
510
5
15

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 515 publications
(554 citation statements)
references
References 46 publications
24
510
5
15
Order By: Relevance
“…They suggested that the textural properties of chalky grain were mainly caused by its relatively high hardness and chewiness. 11) Yamakawa et al (2007) 12) have also described less sticky texture of the high temperature-stressed chalky grains. Singh et al (2003) 6) described that the maximum force and chewiness of cooked rice of chalky grains was smaller than those of the translucent grains, while the chalky grains showed the higher conclusion temperature, Tc1, and the higher endothermic enthalpy, H1, of starch gelatinization by differential scanning calorimetry (DSC) compared with the translucent grains.…”
Section: Breaking Test Of Cooked Rice Of Perfect and Chalky Grainsmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that the textural properties of chalky grain were mainly caused by its relatively high hardness and chewiness. 11) Yamakawa et al (2007) 12) have also described less sticky texture of the high temperature-stressed chalky grains. Singh et al (2003) 6) described that the maximum force and chewiness of cooked rice of chalky grains was smaller than those of the translucent grains, while the chalky grains showed the higher conclusion temperature, Tc1, and the higher endothermic enthalpy, H1, of starch gelatinization by differential scanning calorimetry (DSC) compared with the translucent grains.…”
Section: Breaking Test Of Cooked Rice Of Perfect and Chalky Grainsmentioning
confidence: 99%
“…13,16) More precisely with an HPAEC-PAD technique, Umemoto et al 33) observed increased and decreased percentages of chains of DP 6-13 and DP 20-27 and 44-54, respectively, at lower temperatures during grain- 18) The chalkiness of ae mutant was overcome by transforming the wild-type BEIIb gene, 19) suggesting that the unusual expression of BEIIb is one of key factors causing the chalking of grain. However, Yamakawa et al (2007) 12) have mentioned that, judging from the data obtained using a series of high temperature tolerant and sensitive cultivars, the reduction of amylose content and the increase of long B chains of amylopectin by high temperature were not correlated to the grain chalkiness. Thus, the relevance of the starch fine structure to the chalkiness of grain under high temperature stress is obscure yet.…”
Section: Breaking Test Of Cooked Rice Of Perfect and Chalky Grainsmentioning
confidence: 99%
“…So far, the majority of studies with respect to grain chalkiness have been focused on starch, relating its accumulation or degradation to the formation of chalky tissue (Yamakawa et al, 2007;Fitzgerald et al, 2009). By contrast, the role of the other main component, the proteins, had been underestimated.…”
Section: Role Of Protein Bodies In Chalkiness Occurrencementioning
confidence: 99%
“…In addition, the maximum viscosity and breakdown values were higher, and the final viscosity was low in grains grown at 30ºC. A high temperature was previously reported to enhance the protein content of rice grains (Honjyo, 1971) but decrease the amylose content (Chamura et al, 1979;Yamakawa et al, 2007), and to increase the maximum viscosity and breakdown values (Maeshige, 1984). Our results generally support these previous results, but the protein contents of the milled rice ranged from 5.3% to 5.6% and did not differ significantly between the two temperatures.…”
Section: Cultivarmentioning
confidence: 90%